2013
DOI: 10.3791/50318
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Method of Mouse Lung Intubation

Abstract: A simple procedure to intubate mice for pulmonary function measurements would have several advantages in longitudinal studies with limited numbers or expensive animal. One of the reasons that this is not done more routinely is that it is relatively difficult, despite there being several published studies that describe ways to achieve it. In this paper we demonstrate a procedure that eliminates one of the major hurdles associated with this intubation, that of visualizing the trachea during the entire time of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 8 publications
(8 reference statements)
0
34
0
Order By: Relevance
“…Increasing amounts (0.1 μg, 1.0 μg or 5.0 μg) of mRNA-LNPs in Dulbecco’s Phosphate Buffered Saline (PBS) were injected into animals intradermally (30 μl), intraperitoneally (200 μl), subcutaneously (200 μl), intramuscularly (30 μl) and intravenously (100 μl) with 3/10cc insulin syringes (BD Biosciences) using standard techniques 16 . A Penn-Century Microsprayer Aerosolizer (Model IA-1C) and FMJ-250 high pressure syringe was used for intratracheal delivery of mRNA-LNPs via intubation 17 .…”
Section: Methodsmentioning
confidence: 99%
“…Increasing amounts (0.1 μg, 1.0 μg or 5.0 μg) of mRNA-LNPs in Dulbecco’s Phosphate Buffered Saline (PBS) were injected into animals intradermally (30 μl), intraperitoneally (200 μl), subcutaneously (200 μl), intramuscularly (30 μl) and intravenously (100 μl) with 3/10cc insulin syringes (BD Biosciences) using standard techniques 16 . A Penn-Century Microsprayer Aerosolizer (Model IA-1C) and FMJ-250 high pressure syringe was used for intratracheal delivery of mRNA-LNPs via intubation 17 .…”
Section: Methodsmentioning
confidence: 99%
“…If continuous repeated instillations are required or if repeated pulmonary function tests are needed, another intubation approach may be more desirable 13,14 .…”
Section: Discussionmentioning
confidence: 99%
“…Such techniques appear to be largely successful but they are quite expensive and require intense training for the operator. Notably, Das et al reported a simplified approach for intubating mice in longitudinal studies where the study involved limited number of expensive research animals [24]. They demonstrated usage of fiber-optic light source to visualize trachea which makes the technique convenient to the researcher and aids in measurement of lung mechanisms for relatively longer duration (approximately several weeks) [24].…”
Section: Clinical Utility Of Balf Collectionmentioning
confidence: 99%
“…Notably, Das et al reported a simplified approach for intubating mice in longitudinal studies where the study involved limited number of expensive research animals [24]. They demonstrated usage of fiber-optic light source to visualize trachea which makes the technique convenient to the researcher and aids in measurement of lung mechanisms for relatively longer duration (approximately several weeks) [24]. Crucially, this method could facilitate repeated BALf collection in rats that could reveal real time cellular/cytokine profile changes in the models of chronic respiratory diseases [25].…”
Section: Clinical Utility Of Balf Collectionmentioning
confidence: 99%